Rhinoscleroma: A Case Report - K.M. Hiwale1 , Harshala Lokhande2 , Sunita Vagha3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Rhinoscleroma is a chronic granulomatous disease caused by gram negative bacteria;Klebsiellarhinoscleromatis. Respiratory mucosa is predominantly affected involving mainly the nasal cavityand nasopharynx and further extending to the respiratory tract. Systemic involvement is rare. The bacilli canbe stained for histopathological examination by Hand E, Gram’s stain and Giemsa stain. Treatment beingantibiotics and anti-inflammatory drugs.Case Presentation: Hereby presenting a case of 52 year old male with nasal blockage; clinically found tohave a mass encasing the bilateral chonchae and nasopharyngeal wall being investigated for malignancy, butproved to be diagnosed with rhinoscleroma on histopathology.Conclusion: Rhinoscleroma, usually difficult to diagnose, may be confused with granulomatous disease,carcinoma, tuberculosis and leprosy. Seen majorly affecting the respiratory tract, adequate biopsy materialsent for histopathology may prove to be useful in the diagnosis; along with a proper clinical history. Thepresence of inflammatory background containing Mikulicz cells are highly suspicious of rhinoscleroma. Thedisease often presents with nasal mass therefore clinically mimics with neoplastic mass. Due to its chroniccourse, it often proves challenging to treat. Early diagnosis thus ensures timely treatment further avoidingrelapses and complications.